Student Seating Position and Their Academic Performance in Computer Science Major - Gisela Kurniawati; Oscar Karnalim; Setia Budi (Universitas Multimedia Nusantara, 2021)
A number of studies regarding the correlation between student seating position and their academic performance have been conducted. However, only a few of them focusing on computer science major, which is argued to be unique in terms of teaching style and classroom layout; as the discipline puts more emphasise on hands on activity like programming, system and network configuration. Further, among those works focusing on that major, none of them specifically address undergraduate students. This paper presents an observational study involving 426 computer science undergraduate students. The study covers student activity over one academic semester. A questionnaire survey measuring student awareness about that correlation in their seating preference was also performed, with 126 students as the respondents. In general, the correlation only exists on some circumstances like student major and lecture time. Further, the seating preference can be driven by the awareness of that correlation with some motivating factors like friends, whiteboard position, and personal habit. Per occasion, it is suggested to analyse the class circumstances and the student motivating factors prior performing further actions. Index Terms— seating position; academic performance; observational study; survey instrument; computing education